Reconceptualising the ISMUBA Curriculum Through Integrated Curriculum Development Principles: A Narrative Review - Ali Matsubir; Romelah (Education Specialist, 2025)
The ISMUBA curriculum, consisting of Al-Islam, Kemuhammadiyahan, and Arabic Language, is a distinctive curriculum identity within Muhammadiyah education in Indonesia. Although ISMUBA has a strategic role in shaping religious understanding, Muhammadiyah literacy, Arabic literacy, moral character, and social responsibility, its development is often discussed in a fragmented way. This narrative review reconceptualises ISMUBA curriculum development by synthesising curriculum theory, Islamic education scholarship, Muhammadiyah educational thought, multicultural pedagogy, and contemporary digital learning literature. The article argues that ISMUBA renewal should be grounded in five interrelated foundations: theological and Muhammadiyah-ideological orientation, philosophical orientation, psychopedagogical orientation, socio-cultural and multicultural orientation, and scientific-digital orientation. These foundations should not be treated as separate curriculum components but as mutually reinforcing lenses for defining learning outcomes, selecting content, organising learning progression, designing pedagogy, strengthening assessment, preparing teachers, and evaluating curriculum relevance. The review also argues that ISMUBA should be positioned not only as a cluster of religious and Arabic subjects but also as a formation project that connects faith, knowledge, character, citizenship, organisational identity, and ethical participation in digital society. The article contributes to the scholarship of Islamic education by shifting the discussion of ISMUBA from descriptive implementation toward integrated curriculum reasoning. Practically, the proposed synthesis can support Muhammadiyah schools, curriculum designers, and ISMUBA teachers in developing learning that is faithful to Islamic values, rooted in Muhammadiyah identity, responsive to Indonesian pluralism, and relevant to contemporary educational change.